Micronecta poweri (Douglas & Scott) in Slovenia (Heteroptera: Corixidae) - Gogala, Andrej (Acta entomologica slovenica (Ljubljana), 2009)
A lesser boatman species Micronecta poweri (Douglas & Scott, 1869) was discovered in the Višnjica stream near Krka in the pre-Dinaric region of Slovenia. This is the first reliable record of the species in Slovenia.
Keywords: entomologija; favna; Heteroptera; Slovenia; Slovenija; zoogeografija